European women’s perceptions of the implementation and organisation of risk-based breast cancer screening and prevention: a qualitative study - Linda Rainey; Daniëlle van der Waal; Anna Jervaeus; Louise S. Donnelly; D. Gareth Evans; Mattias Hammarström; Per Hall; Yvonne Wengström; Mireille J. M. Broeders (BMC Cancer, 2020)
Abstract Background Increased knowledge of breast cancer risk factors has meant that we are currently exploring risk-based screening, i.e. determining screening strategies based on women’s varying levels of risk. This also enables risk management through primary prevention strategies, e.g. a lifestyle programme or risk-reducing medication. However, future implementation of risk-based screening and prevention will warrant significant changes in current practice and policy. The present study explores women’s perceptions of the implementation and organisation of risk-based breast cancer screening and prevention to optimise acceptability and uptake. Methods A total of 143 women eligible for breast cancer screening in the Netherlands, the United Kingdom, and Sweden participated in focus group discussions. The focus group discussions were transcribed verbatim and the qualitative data was analysed using thematic analysis. Results Women from all three countries generally agreed on the overall proceedings, e.g. a risk assessment after which the risk estimate is communicated via letter (for below average and average risk) or consultation (for moderate and high risk). However, discrepancies in information needs, preferred risk communication format and risk counselling professional were identified between countries. Additionally, a need to educate healthcare professionals on all aspects of the risk-based screening and prevention programme was established. Conclusion Women’s insights identified the need for country-specific standardised protocols regarding the assessment and communication of risk, and the provision of heterogeneous screening and prevention recommendations, monitoring the principle of solidarity in healthcare policy.